Transforming Food Production: A Review of Extrusion Technology and its Applications - Dr. Prerana Shere; Dr. Rinku Agrawal (Extrusion Technology: Transforming Food Processing, 2024)
The modern lifestyle and changing food consumption patterns have created a demand for nutritionally upgraded food products without compromising the sensory attributes of the products. The food industry and food scientists are continuously developing a new era of food products and processing technologies. One such technology is “extrusion” in which the mixed food ingredients are squeezed through a die under differential pressure and temperature to produce a variety of food products.